Analysis Of Employee Job Satisfaction With Work Stress, Work Environment And Work Life Balance As Predictors At CV Imexindo Nusantara - Andhi Supriyadi; Rumanul Hidayat (International Conference On Digital Advanced Tourism Management And Technology, 2023)
Employees must be effectively managed as a valuable asset for a firm in order to maximize their contribution. Psychological factors relating to employee psychology, social factors relating to social interactions between employees and their superiors and coworkers, financial factors relating to employee salaries, and physical factors relating to timing, rest time, and conditions of the work environment are factors which influence employee job satisfaction. This study was conducted at CV IMEXINDO NUSANTARA, and a sample of up to 112 employees out of 155 was used. The analysis's findings indicate that factors including stress at work, the workplace environment, and work-life balance have an impact on job satisfaction variables in CV IMEXINDO NUSANTARA both alone and jointly